PERSEPSI KOMUNITAS PENGGUNA AIRBNB PADAP VALUE PROPOSITION AIRBNB (Studi Pada Komunitas Pengguna Airbnb di Kota Malang) - Elva Noverina Putri; Mohammad Iqbal; Brillyanes Sanawiri (Jurnal Administrasi Bisnis, 2018)
The development of technology and information today makes a variety of things as something that can be used simultaneously. The growing trend of Sharing Economy and Collaborative Consumption in the world makes the community easier to access anything, anywhere, and anytime. This makes Airbnb a place to find the widest accommodation that can reach across the world. Airbnb has a community of users who will be interconnected with each other and mutually beneficial. This study aims to determine the perception of Airbnb users in Malang about Value Proposituon contained in the application Aiebnb. Data collection techniques used are observation, interviews, and documentation and use descriptive qualitative research type. Based on the value proposition according to Alexander Ostewalder and Yves Pigneur, there are eleven elements and in Airbnb application has seven of them are novelty, adjustment, design, price, cost reduction, accessability, and convenience and usability. Kеywords: Airbnb, Value Proposition, Sharing Economy, Collaborative Consumption, ConsumerPerseption АBSTRАK Berkembangnya teknologi dan informasi saat ini menjadikan berbagai macam hal sebagai sesuatu yang dapat dipakai secara bersamaan. Maraknya tren Sharing Economy dan Collaborative Consumption di dunia menjadikan masyarakat lebih mudah untuk mengakses apapun, dimanapun, dan kapanpun. Hal ini menjadikan Airbnb sebagai wadah untuk mencari akomodasi terluas yang dapat menjangkau di seluruh dunia. Airbnb memiliki sebuah komunitas pengguna yang akan saling berhubungan satu sama lain dan saling menguntungkan.Penelitian ini bertujuan untuk mengetahui persepsi para pengguna Airbnb di Kota Malang tentang Value Proposituon yang terdapat pada aplikasi Aiebnb. Teknik pengumpulan data yang digunakan adalah observasi, wawancara, dan dokumentasi serta menggunakan jenis penelitian kualitatif deskriptif. Berdasarkan value proposition menurut Alexander Ostewalder dan Yves Pigneur, terdapat sebelas elemen dan dalam aplikasi Airbnb memiliki tujuh diantaranya yaitu sifat kebaruan, penyesuaian, desain, harga, pengurangan biaya, kemampuan dalam akses, serta kenyamanan dan kegunaan. Kаtа Kunci: Airbnb, Value Proposition, Sharing Economy, Collaborative Consumption, Persepsi Konsumen.